The impact of proton pump inhibitors on brain health based on cross-sectional findings from the Rhineland Study - Nersi Alaeddin; Alexandra Koch; Rika Etteldorf; Julia C. Stingl; Monique M.B. Breteler; Folgerdiena M. de Vries (Scientific Reports)
Abstract Reports linking proton pump inhibitors (PPIs) with cognition and dementia show conflicting results, with limited evidence on underlying biological mechanisms. However, existing studies did not investigate brain microstructure, which could provide valuable insights into early structural changes indicative of cognitive decline. Analyses were based on cross-sectional baseline data from the Rhineland Study (n = 7,465; mean age 55.3 ± 13.7 years, range 30–95 years, 56.5% women). Using multivariate linear regression, we investigated associations between PPI use and cognition and brain macro- and microstructural measures (fractional anisotropy (FA) and mean diffusivity (MD) as measures of white matter integrity). Analyses were stratified by short-term (< 3 years) and long-term (≥ 3 years) PPI use, with additional age stratification (< 65 years; ≥65 years) for cognitive outcomes. PPI users, especially younger individuals, showed poorer global cognition and working memory. Notably, younger long-term users had worse total memory. PPI use was not associated with brain volume or FA, but both short-term and long-term users showed higher MD in cognitive-related brain regions. Our findings indicate that prolonged PPI use, particularly in younger long-term users, is associated with poorer cognitive performance. Moreover, PPI users showed higher MD, indicating potential white matter integrity disruptions. Further research is needed to ascertain causality and underlying mechanisms behind PPI-related cognitive decline.